COSO Model-based Control of an IT Environment - Babuśka, Ewa Wiktoria (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The article presents internal control in an IT environment done in accordance with the COSO model and emphasises the importance of the control to an entity’s internal control systems. The paper describes the key components of internal control including relevant IT aspects. It also explains general and application controls employed as the main information processing controls. The final section characterises the functions, objectives and control tasks in the IT environment.